We know that in a triangle, if one side of it is produced, then
Exterior angle = sum of its interior opposite angles
(i) In Fig. (i), 110° = x° + 30°
⇒ x° = 110° - 30° = 80°
(ii) In Fig. (ii), 120° = y° + 60°
⇒ y° = 120° - 60° = 60°
(iii) In Fig.(iii), 122° = k° + 35°
⇒ k° = 122° - 35° = 87°
(iv) In Fig. (iv), 135° = a° + 73°
⇒ a° = 135° - 73° = 62°
(v) In Fig. (v), 125° = a + c ….(i)
And 140° = a + b …..(ii)
Adding, we get
a + c + a + b = 125° + 140°
⇒ a + a + b + c = 265°
But a + b + c = 180°
(Sum of angles of triangles)
∴ a + 180° = 265°
⇒ a = 265° - 180° = 85°
But a + b = 140°
⇒ 85° + b = 140°
⇒ b = 140° - 85° = 55°
And a + c = 125° ⇒ 85° + c = 125°
⇒ c = 125° - 85° = 40°
Hence, a = 85°, b = 55° = 40°
(vi) In Fig. (vi)
112° + x° = 180° (Linear pair)
⇒ x = 180° - 112° = 68°
And 112° = y + 63°
⇒ y = 112° - 63° = 49°
Hence x = 68°, y = 49°
(vii) In Fig. (vii),
120° = a + a ⇒ 2a = 120°
⇒ a = 120°/2 = 60°
∴ a = 60°
(viii) In Fig. (viii),
140° + a = 180° (Linear pair)
⇒ a = 180° - 140° = 40°
Now, 4m = 2m = a ⇒ 4m – 2m = a
⇒ 2m = 40° ⇒ m = 40°/2 = 20°
Hence, m = 20°
(ix) In Fig. (ix),
105° = b + b ⇒ 2b = 105°
⇒ b = 105°/2 = 52.5°
But a + 105° = 180° (Linear pair)
⇒ a = 180° - 105° = 75°
Hence a = 75° , b = 52.5°